2012
DOI: 10.4236/ajac.2012.31001
|View full text |Cite
|
Sign up to set email alerts
|

Comparison between Two FT-IR Spectroscopy Analytical Procedures for Micrograms Determination of Asbestos Species in Bulk Materials

Abstract: The Fourier Transform Infrared (FT-IR) spectroscopy is by far known to be a useful technique for qualitative and quantitative analysis of asbestos in bulk samples, since all asbestos species exhibit intense absorption peaks in the 4000 -400 cm -1 region of the infrared spectrum. In the present work, we compare the accuracy and precision of two analytical procedures (the Linear Calibration Curve Method and the Method of Addition) for the quantitative determination of asbestos in a host matrix. We have found tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 9 publications
0
6
0
Order By: Relevance
“…Chrysotile shows double O–H peaks stronger at about 3685 cm −1 and weaker at 3655 cm −1 [ 26 ]. A broad O–H bending band is present at 605 cm −1 , Si–O stretching vibration at 1069, 1033 and 959 cm −1 , and evident bands at about 606, 434 and 300 cm −1 can be assigned to Mg–OH bending frequency [ 20 , 25 ].…”
Section: Theorymentioning
confidence: 99%
See 2 more Smart Citations
“…Chrysotile shows double O–H peaks stronger at about 3685 cm −1 and weaker at 3655 cm −1 [ 26 ]. A broad O–H bending band is present at 605 cm −1 , Si–O stretching vibration at 1069, 1033 and 959 cm −1 , and evident bands at about 606, 434 and 300 cm −1 can be assigned to Mg–OH bending frequency [ 20 , 25 ].…”
Section: Theorymentioning
confidence: 99%
“…Quantitative analyses using calibration curves are based upon measuring a property of a sample that changes with the analyte concentration [ 20 ]: in the present case, the calibration curves are obtained by plotting the height of the absorption peak, h M , as a function of the concentration, C x ; i.e. , h M = A + B C x .…”
Section: Theorymentioning
confidence: 99%
See 1 more Smart Citation
“…This discrepancy may be possibly due to: (1) interference of antigorite and chlorite present in the investigated samples with a severe overlap of their absorption bands to that of chrysotile, and (2) deviation of the linearity of the curve intensity of the chrysotile absorption band vs. concentration for large chrysotile contents. The breaking of the linearity assumption has been already observed by De Stefano et al (2012). They observed that in the case of chrysotile, the peak intensity is a quadratic-like function of the concentration in the extended concentration range.…”
Section: Accuracy Of Results From the Various Experimental Techniquesmentioning
confidence: 68%
“…In this work, benchtop micro-XRF was utilized to identify and classify asbestos fibers (Bonifazi et al, 2015;Bonifazi et al, 2018). The proposed strategy, based on the combined use of micro-XRF imaging and chemometric techniques, can be a valid and efficient analytical approach supporting the currently adopted asbestos recognition techniques, such as Fourier transform infrared spectroscopy (FT-IR) (De Stefano et al, 2012), Raman spectroscopy (Petriglieri et al, 2015), polarized light microscopy (PLM) (Lee et al, 2008) and scanning electron microscopy (SEM) (Gandolfi et al, 2016). All these techniques require the preparation of samples and usually allow punctual measurements and/ or small areas mapping.…”
Section: Introductionmentioning
confidence: 99%